2008
DOI: 10.1186/1472-6831-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Minimising barriers to dental care in older people

Abstract: BackgroundOlder people are increasingly retaining their natural teeth but at higher risk of oral disease with resultant impact on their quality of life. Socially deprived people are more at risk of oral disease and yet less likely to take up care. Health organisations in England and Wales are exploring new ways to commission and provide dental care services in general and for vulnerable groups in particular. This study was undertaken to investigate barriers to dental care perceived by older people in socially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
124
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(134 citation statements)
references
References 21 publications
6
124
0
4
Order By: Relevance
“…Lastly, similar to the study conducted by Borreani and Wright, the results of our study identified cost on transportation as the biggest indirect cost inferred by this age group [19,20]. This was especially true for individuals who did not have a family support to bring them for their dental treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Lastly, similar to the study conducted by Borreani and Wright, the results of our study identified cost on transportation as the biggest indirect cost inferred by this age group [19,20]. This was especially true for individuals who did not have a family support to bring them for their dental treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Kwetsbaarheid heeft een negatieve invloed op zowel tandartsbezoek als op mondverzorgingsgedrag (MacEntee, 2011). Onderzoek heeft aangetoond dat verminderde mobiliteit, verminderde fysieke functies, weinig energie, depressie en gebrek aan sociale steun hiermee zijn geassocieerd (Dolan et al, 1998; Kiyak en Reichmuth, 2005;Borreani et al, 2008;Stromberg et al, 2012). Niet bekend is op welke manier kwetsbaarheid en verschillende kwetsbaarheidsfactoren van invloed zijn op de mondverzorging en tandartsbezoek van ouderen.…”
Section: Inleidingunclassified
“…Algemeen erkende barrières voor tandartsbezoek door ouderen, zoals 'beschikbaarheid',' bereikbaarheid', 'kosten', 'afhankelijkheid van anderen' en in sommige gevallen zelfs 'gepercipieerde orale problemen' lijken van ondergeschikt belang te zijn voor de geïnterviewde groep ouderen (Holm-Pedersen et al, 2005;Kiyak en Reichmuth, 2005;Borreani et al, 2008;Brothwell et al, 2008). Zelfs toen de interviewers meldden dat het wellicht mogelijk zou zijn om op locatie door een tandarts te worden bezocht, zeiden de meeste mensen die geen tandarts meer bezochten, dat ze niet wisten of ze van een dergelijke service wel gebruik zouden maken.…”
Section: Discussieunclassified
“…Furthermore, the level of private care is shifting fast, new UK graduates are increasingly fi nding it diffi cult to get jobs in areas of their choice, and the historical fl exibility in the system has reduced with devolved budgets for dentistry. Third, many of the assumptions such as the level of care provided for older people assume that the current level of demand is appropriate to need, whereas that is patently not the case for older people: uptake is low, barriers to dental care are multiple, 43 and there is unmet need.…”
Section: Limitations Of the Projectmentioning
confidence: 99%